Development of an Educational Training Game for Ear Sensitivity of Intervals - Salim, Michael Nagaku Milenn; Maulana, Hanhan (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2023)
This study aims to build a game to help beginner musicians in the process of training ear sensitivity to intervals without involving the teacher in the training process. The software development uses the Multimedia Development Life Cycle (MDLC) method. A software is built in the form of a game that can train the ear's sensitivity to intervals, share knowledge related to intervals, randomize questions and validate answers without involving the teacher in the learning process. The average respondents' answers related to the application were positive. It can be concluded that the development of the application can help users in training the ear sensitivity to intervals and increase the user's knowledge of music theory, especially related to intervals.